HUSSERL, Edmund (2019). Textos Breves (1887-1936). Coord.: Agustín Serrano de Haro y Antonio Zirión Quijano. Salamanca: Sígueme. - Marcos, Jesús Miguel (Daimon Revista Internacional de Filosofia, 2021)
Reseña de: HUSSERL, Edmund (2019). Textos Breves (1887-1936). Coord.: Agustín Serrano de Haro y Antonio Zirión Quijano. Salamanca: Sígueme.